The importance of authentic workplace-based assessment: A study from VET teacher education - Jorunn Dahlback; Hanne Berg Olstad; Ann Lisa Sylte; Anne-Catrine Wolden (International Journal for Research in Vocational Education and Training (IJRVET), 2020)
Context: This article is based on a pragmatic theoretical perspective on education, in which theoretical and practical competences are developed through experiences and participation in real-world teaching contexts. Previous research points to a lack of culture for authentic workplace-based assessment in vocational and professional education in many countries. Prior to this study, professors/authors and student-teachers in a vocational teacher education program in Norway experienced that student-teachers were unable to demonstrate comprehensive teaching competence, as examinations and assessments assess theoretical knowledge separately from practice. Research questions: 1) How can an authentic workplace-based exam during placement give student-teachers an opportunity to showcase their comprehensive teacher competence? 2) What factors are important to emphasize in such an exam? 3) How do the student-teachers demonstrate and develop comprehensive teacher competence through an authentic exam? Methods: Using action research, professors/authors carried out sequential actions to develop a practical-theoretical exam in an authentic professional setting. This included demonstrating elements of practical and theoretical competence conducted during teaching practice. The exam involved planning in line with a guidance document and practical teaching in the classroom in VET-schools, followed by a piece of reflective writing based on teaching experiences. Supervisors and professors/authors observed the student-teachers teaching as part of multiple qualitative methods. Findings: The empirical results show how student-teachers demonstrate and develop comprehensive teaching competence. Both the student-teacher and the supervisors in VET-schools experienced the authentic exam as realistic and professionally based. The biggest challenge involved logistics: Compensating the professors'/authors' time and financial frameworks related to the observation of the student-teachers. However, this kind of authentic assessment leads to stronger coherence between both theory and practice, and between the vocational teacher education at the university and the VET in upper secondary school. It also supports the job-relevant learning process towards comprehensive teacher competence. Conclusions: This kind of authentic assessment i.e. an authentic exam requires an understanding of the complex role of teachers within their professional context in VET. Therefore, the professors/authors see the need of a broader, more comprehensive teacher competence in VET to meet the work life needs for competence.
Keywords: 330; Comprehensive Teacher Competence; Relevance; Coherence; Work-Based Education; Competence-Based Exam; Vocational Education and Training; VET; Work-Based Assessment